Identification of critical residues of linear B cell epitope on Goodpasture autoantigen. - Xiao-yu Jia; Zhao Cui; Jian-nan Li; Shui-yi Hu; Ming-hui Zhao (PLoS ONE, 2015)
BACKGROUND:The autoantigen of anti-glomerular basement membrane (GBM) disease has been identified as the non-collagenous domain 1 of α3 chain of type IV collagen, α3(IV)NC1. Our previous study revealed a peptide on α3(IV)NC1 as a major linear epitope for B cells and potentially nephrogenic, designated as P14 (α3129-150). This peptide has also been proven to be the epitope of auto-reactive T cells in anti-GBM patients. This study was aimed to further characterize the critical motif of P14. METHODS:16 patients with anti-GBM disease and positive anti-P14 antibodies were enrolled. A set of truncated and alanine substituted peptides derived from P14 were synthesized. Circulating antibodies against the peptides were detected by enzyme linked immunosorbent assay (ELISA). RESULTS:We found that all sera with anti-P14 antibodies reacted with the 13-mer sequence in the C-terminus of P14 (P14c) exclusively. The level of antibodies against P14 was highly correlated with the level of antibodies against P14c (r=0.970, P<0.001). P14c was the core immunogenic region and the amino acid sequence (ISLWKGFSFIMFT) was highly hydrophobic. Each amino acid residue in P14c was sequentially replaced by alanine. Three residues of glycine142, phenylalanine143, and phenylalanine145 were identified crucial for antibody binding based on the remarkable decline (P<0.001) of antibody reaction after each residue replacement. CONCLUSIONS:We defined GFxF (α3142, 143,145) as the critical motif of P14. It may provide some clues for understanding the etiology of anti-GBM disease.